2020
DOI: 10.1177/0886260520916831
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Rape Myth Acceptance and Sexual Behaviors

Abstract: An extensive amount of research has been devoted to understanding rape myths, especially in the context of sexual attitudes. Few studies have examined sexual actions as a correlate of rape myth acceptance (RMA). As such, this study utilizes the Updated Illinois Rape Myth Acceptance Scale (IRMA) and its four distinct subscales to examine adherence to rape myths and an individual’s view of sex and sexuality in a sample of 1,310 college students. The IRMA was included in its entirety and separated into its four s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 55 publications
2
9
0
Order By: Relevance
“…Indeed, leading researchers have postulated that overt sexism and rape myth acceptance has become increasingly frowned upon in our culture (McMahon & Farmer, 2011). However, it is clear that men are still more likely to report adherence to rape supportive beliefs (Fansher & Zedaker, 2022), suggesting that it is perhaps more likely that this finding reflects men’s tendency to report witnessing more events that would warrant intervention to ensure the safety of their acquaintances. This finding may be more representative of the social desirability of reporting that individuals are witnessing potential events as a bystander, and less a change in the behavioral patterns of male participants.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, leading researchers have postulated that overt sexism and rape myth acceptance has become increasingly frowned upon in our culture (McMahon & Farmer, 2011). However, it is clear that men are still more likely to report adherence to rape supportive beliefs (Fansher & Zedaker, 2022), suggesting that it is perhaps more likely that this finding reflects men’s tendency to report witnessing more events that would warrant intervention to ensure the safety of their acquaintances. This finding may be more representative of the social desirability of reporting that individuals are witnessing potential events as a bystander, and less a change in the behavioral patterns of male participants.…”
Section: Discussionmentioning
confidence: 99%
“…Both the original IRMA and its updated version have been, and still are, widely used in research today (e.g. Canan et al, 2018;Carroll et al, 2016;Fansher & Zedaker, 2020;Hayes et al, 2013;Navarro & Tewksbury, 2017;Newins et al, 2018). However, despite their widespread use, measuring contemporary prejudiced attitudes using measures which were created decades ago can be problematic.…”
Section: Measurement Of Rape Mythsmentioning
confidence: 99%
“…Organized sport has been historically described as a masculinity‐validating experience (Dubbbert, 1979), based on the bonding of male athletes, physicality of the activity and sanctioning of violence (Messner, 1990). While sport is commonly associated with hegemonic, toxic masculinity (Fansher & Zedaker, 2022; McCray & Taylor, 2021), which emphasizes men in a position of power and privilege, participants associated their engagement in sport with characteristics of healthy masculinity such as respect, confidence, persistence and leadership. These findings support literature which has pointed to athletics as a setting and platform that can create Black leaders and give them voice, particularly within the Black muscular Christianity tradition (Harrison et al, 2020; Putz, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Boeringer (1999) found that male athletes are more likely to agree with rape‐supportive statements than fraternity members, yet both groups are significantly more likely to do so than individuals outside these social settings. More recently, being a college athlete—as well as being younger—was found to be associated with high scores of rape myth acceptance (Fansher & Zedaker, 2022). However, adherence to hegemonic values and toxic traits is destructive for all people.…”
Section: Introductionmentioning
confidence: 99%